The Influence of Stress as a Mediator in the Relationship between Role Conflict and Burnout - Mhd. Hanif Zulhapiz (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
This study aims to analyze the influence of stress as a mediating factor in the relationship between role conflict and burnout. The research was conducted on a population of students who study while working in Sungai Penuh City, Jambi Province, with a sample size of 70 individuals, collected using purposive sampling. The research results were processed using the SMART-PLS application, employing procedures such as Measurement Model Assessment (MMA), R Square, Q Square, and Structural Model Assessment (SMA). The findings of this research indicate that role conflict has a positive effect on burnout, role conflict has a positive effect on stress, stress has a positive effect on burnout, and stress mediates the relationship between role conflict and burnout positively